(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This paper explores modern China’s national memory through the lens of the Zhouyi. Traditional Chinese historiography often regards ancient China as a golden age. In the 20th century, the Doubting Antiquity School, led by Gu Jiegang, questioned this perspective, advocating for a reevaluation of ancient Chinese texts. During this period, many scholars revisited these ancient texts. This paper finds that 20th-century Yi-ology exhibited a tendency toward "telling Chinas story well," as scholars used the Zhouyi to reconstruct a new ancient historical discourse. This discourse, while based on ancient history, served 20th-century China with the goal of reshaping modern China’s national memory. The paper introduces the 20th-century research achievements in Zhouyi studies and examines the original significance of Yi during the Zhou Dynasty, which is crucial for understanding why Zhouyi has consistently been regarded as a Chinese canon. Finally, it argues that the Zhouyi has played a significant role in shaping China’s national identity by reconstructing national memory through the 20th-century discourse.